Legal System Corporate Complex - Gachi, Allel (Journal of Legal Studies and Researches, 2020)
The economy of any country depends on projects, which lead to the reduction or elimination of unemployment. Project clustering is a form of economic focus that is not prohibited in itself. The complex of companies is a group of companies legally independent and linked to economic ties, as this complex does not acquire moral character. The parent company exercises its legal and actual control over the rest of the other companies, thus leading to a decision-making unit.